Online Archives for Users: premises for a Quality Reference Model - Feliciati, Pierluigi; Alfier, Alessandro (JLIS.it, 2017)
The traditional paradigm of archival mediation had to come to grips with the web environment. If guides, inventories and indexes act as mediation tools between what is inside archives and whoever needs to access them, traditional archival finding aids are not ready to be published on the web, where users are basically free from any mediation. The starting point for rethinking the archival mediation paradigm could be the principle that “output is not input” (Sheir 2005), and the compliance to current archival standards is a necessary condition, but not sufficient to guarantee the usability of archives online. Rarely archival projects organize specific user studies to finalize language, interfaces and architectures of the new environments. The paper, based also on a huge research with user studies on an archives online prototype, aims to propose some first elements to guide the drawing of a new model, built to ensure quality to archives online in terms of user needs, experience and satisfaction, and presents the case study of evaluation of a huge archival portal based on an user-centred approach, during the formative phase.